Growth Promotion of Oil Palm Seedlings (Elaeis guineensis Jacq.) with Slow-Release Fertilizer Application - Harahap, Adiansyah; Hariyadi; Junaedi, Ahmad; Prasetyo, Lilik Budi (Journal of Tropical Crop Science, 2025)
Oil palm (Elaeis guineensis Jacq.) is a major source of vegetable oil and an important plantation commodity in the Indonesian economy. This study aims to determine the effect of slow-release fertilizer on the growth of oil palm seedlings in the primary nursery and to determine the nutrient status through laboratory analysis and spectroradiometer. The study was conducted at the IPB experimental station in Cikabayan, Dramaga, Bogor. Analysis of soil and leaf samples at the AGH Test Laboratory of the IPB University Department from December 2023 to July 2024. This study used a complete randomized block design with one factor, a nine-level fertilizer dose, and was repeated four times. Each experimental unit has 10 plants, so the total plant population is 360. Slow-release fertilizer can supply nutrients for a period of weeks. This study tested if it would benefit the growth of oil palm seedlings in the primary nursery. A slow-release fertilizer dose of 75% provides the best increase in oil palm seedling growth, whereas, at 50 and 150% doses, it did not increase compared to the control. The agronomic effectiveness value is above 95%.